2023
DOI: 10.1002/smll.202303539
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized Anionic Redox by Rational Structural Design from Surface to Bulk for Long‐Life Fast‐Charging Li‐Rich Oxide Cathodes

Abstract: On account of high capacity and high voltage resulting from anionic redox, Li‐rich layered oxides (LLOs) have become the most promising cathode candidate for the next‐generation high‐energy‐density lithium‐ion batteries (LIBs). Unfortunately, the participation of oxygen anion in charge compensation causes lattice oxygen evolution and accompanying structural degradation, voltage decay, capacity attenuation, low initial columbic efficiency, poor kinetics, and other problems. To resolve these challenges, a ration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…Therefore, distinct diffraction peaks observed between 20° and 25° indicate that both the pristine LRNMO and its modified sample with an ordered structure of excessive Li + in the TM layer have been successfully synthesized. Furthermore, the clear separation of the (108)/(110) and (006)/(102) diffraction peaks demonstrates the high crystallinity and layered structure of the materials. , The ratio of the intensity of the (003) peak to the (104) peak provides insight into the extent of Li + /Ni 2+ mixing within the layered configuration. The larger the ratio of I (003) to I (104) is, the higher the degree of cation order, and the more stable the structure will be.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, distinct diffraction peaks observed between 20° and 25° indicate that both the pristine LRNMO and its modified sample with an ordered structure of excessive Li + in the TM layer have been successfully synthesized. Furthermore, the clear separation of the (108)/(110) and (006)/(102) diffraction peaks demonstrates the high crystallinity and layered structure of the materials. , The ratio of the intensity of the (003) peak to the (104) peak provides insight into the extent of Li + /Ni 2+ mixing within the layered configuration. The larger the ratio of I (003) to I (104) is, the higher the degree of cation order, and the more stable the structure will be.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the clear separation of the (108)/ (110) and ( 006)/(102) diffraction peaks demonstrates the high crystallinity and layered structure of the materials. 30,31 The ratio of the intensity of the (003) peak to the (104) peak provides insight into the extent of Li + /Ni 2+ mixing within the layered configuration. The larger the ratio of I (003) to I (104) is, the higher the degree of cation order, and the more stable the structure will be.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, previous literature has suggested that boron (B) ions at transition metal (TM) lattice sites easily locate to interstitial sites to form tetrahedral BO 4 , which is more stable than other lattice structures, and Xiao et al combined density functional theory (DFT) and neutron powder diffraction (NPD) experimental results to confirm that B is doped into interstitial sites to form BO 4 structures. 22–25 Therefore, our predictions for doping sites primarily focused on the cerium element. 26–28 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…19 Meanwhile, boron (B) doping significantly affects cathode materials because B dopes into interstitial sites to form strong covalent B–O bonds, resulting in more negative charges on oxygen, thereby reducing oxygen transition oxidation and inhibiting irreversible structural changes during cycling. 20,21 To the best of our knowledge, the synergistic effect of boron and high-valence elements has not been utilized to adjust the internal electronic structure and structural stability of cathode materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The currently widely used lithium-ion batteries (LIBs) might be a candidate for this purpose. [7][8][9][10] However, they will be excluded when the limited lithium resources and underlying political disputes are taken into consideration. [11][12][13] Sodium-ion batteries (SIBs) emerge as promising alternatives due to the omnipresent availability of Na resources.…”
Section: Introductionmentioning
confidence: 99%